La présence et le fonctionnement de l’absence dans le Nouveau Roman - Czesław Grzesiak (Quêtes Littéraires, 2011)
The French nouveau roman is characterised by lack of numerous elements typical of the traditional, commonly called Balzacian, novel. This lack involves the rejection of plot, omniscient narrator, psychological, moral and ideological factors, social and political engagement, the decomposition of character, the indeterminacy and gradual implosion of time and space as well as the text generation based on some lack or void. The aim of the article is to present these missing elements of the represented world and to discuss their functions in the works of leading practitioners of the nouveau roman, such as Samuel Beckett (predecessor), Michel Butor, Marguerite Duras, Robert Pinget, Alain Robbe-Grillet, Nathalie Sarraute and Claude Simon.